Peptide Materials Obtained by Aggregation of Polyphenylalanine Conjugates as Gadolinium‐Based Magnetic Resonance Imaging Contrast Agents. (21st October 2015) - Diaferia, Carlo; Gianolio, Eliana; Palladino, Pasquale; Arena, Francesca; Boffa, Cinzia; Morelli, Giancarlo; Accardo, Antonella
Abstract : Peptide materials based on the aggregation of polyphenylalanine conjugates containing gadolinium complexes and acting as potential contrast agents (CAs) in magnetic resonance imaging (MRI) are described. Monomers contain two (F2) or four (F4) phenylalanine residues for self‐assembly, a chelating agent, 1, 4, 7, 10‐tetraazacyclododecane‐ N, N, N, N ‐tetraacetic acid (DOTA) or diethylenetriaminepentaacetic acid (DTPA), for achieving gadolinium coordination, and ethoxylic linkers at two (L2 ) or six (L6 ) poly(ethylene glycol) (PEG) units between the chelating group and the peptide region. Both DOTA and DTPA tetraphenylalanine derivatives, and their gadolinium complexes DOTA(Gd)‐L6 ‐F4 and DTPA(Gd)‐L6 ‐F4, are able to self‐aggregate at very low concentration. Structural characterization, obtained by circular dichroism and infrared measurements, confirms the amyloid type fibril formation in which an antiparallel peptide alignment is preferred. Amyloid type fibril formation is also observed, in solid state, by transmission electron microscopy images and X‐ray diffraction patterns. The relaxivity values of DOTA(Gd)‐L6 ‐F4 and DTPA(Gd)‐L6 ‐F4 and their ability to enhance the MRI cellular response on the J774A.1 mouse macrophages cell line indicate that these peptide materials are promising candidate as a new class of supramolecular gadolinium based MRI contrast agents. Abstract : Novel peptide materials are proposed as a new class of supramolecular gadolinium based magnetic resonance imaging contrast agents. These materials, containing four phenylalanine residues, a Gd‐DOTA or Gd‐DTPA complex, and a poly(ethylene glycol) spacer, are able to self‐aggregate in amyloid type fibrils with an antiparallel alignment in acqueos solution at very low concentration.